Peningkatan Hasil Belajar Siswa Melalui Strategi Pembelajaran Kooperatif Make a Match Pada Siswa Kelas IV Tentang Qs. Al-Ashr dan Qs. An -Nasr - Muchamad Chaidar (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Based on phenomena in the world of education, students often do not pay attention to the teacher's explanation or even they play alone or chat with their friends during the learning process so that the class becomes noisy and the lessons conveyed by the teacher become ineffective. This is because there are still a few teachers who apply learning models that are appropriate to the learning materials and are in favor of students, but teachers often use traditional methods. The purpose of this classroom action research is to channel students' excessive active attitudes by applying the make a match type cooperative learning model and describing the achievement of student learning outcomes after participating in Al-Qur'an Hadith learning on the subject Qs. Al-Ashr and Qs. An-Nasr class IV at MI Darul Hikam Cirebon academic year. In this study, the subjects of the study were students of Madrasah Ibtidaiyah Darul Hikam City of Cirebon, school year with a total of 36 students. The results of data analysis show that there is an increase in student learning outcomes in learning Qs. Al-Ashr and Qs. An-Nasr class IV at MI Darul Hikam Cirebon City, namely the student learning completeness score in cycle I was 66.66%, and then in cycle II it increased to 83.33%. The value of this learning result is at a level of success in very good criteria. This shows that students have been able to master Qs material. An-Nasr well. The advice given refers to the results of this study, namely schools and teachers to be more intensive in conducting teacher and teacher training. They should be more skilled in observing the characteristics of students and be able to run the make a match type cooperative learning model, so that the learning process is more effective, creative, innovative and fun on the subject of Al-Qur'an Hadith and also on other subjects.